Relationship power and HIV sero-status: an analysis of their relationship among low-income urban Zimbabwean postpartum women - Teurai Rwafa; Simukai Shamu; Nicola Christofides (BMC, 2019)
Abstract Background HIV disproportionately infects women in many regions. Zimbabwe is one of the countries, most heavily affected. Unequal gender power relations between men and women can increase women's vulnerability to HIV. The aim of this paper was to determine the relationship between gender power and HIV sero-status among postpartum women in Zimbabwe. Methodology A cross-sectional survey was conducted among 2042 women aged 15-49 years, attending postnatal-care at six public primary health care clinics in low-income urban communities of Harare in 2011. Women were asked about relationship power factors using an interviewer-administered questionnaire. The questionnaire included adapted WHO multi-country study items, which measure partner violence perpetrated against women. HIV status data were based on rapid HIV diagnostic tests done during earlier antenatal visits. The analysis was restricted to women with known HIV test results (n = 1951). Multivariable logistic regression analyses were performed to assess the predictors of HIV and relationship power factors. Results HIV prevalence was 15.3% (n = 299/1951). Three quarters of the women (76.9%, n = 1438/1871) reported some level of relationship control in their current/most recent intimate relationship. HIV positive women reported higher levels of control by the male partner in their intimate relationships. In adjusted models, the study found a significant association between relationship-control by the male partner and women's HIV status (AOR 1.11, 95% CI 1.01-1.22), and the decision-making dimensions of relationship power. Although there were indications of high male partner control in participants' intimate relationships, some women still had agency, as they were able to make independent decisions to fall pregnant. These women were less likely to be HIV positive (AOR 0.54, 95% CI 0.29-1.00). Having a partner who ever refused use of a family planning method was associated with increased odds of having a positive HIV status among the postpartum women (AOR 1.88, 95% CI 1.20-2.90). Conclusion Unequal gender power relations continue to be a risk factor for heterosexual transmission of HIV. This suggests that prevention efforts have not successfully resulted in gender equality. HIV prevention interventions should address gender power dynamics to help curb the disproportionate HIV burden among women.